2017
DOI: 10.1016/j.ijsu.2017.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Comparing quality of life outcomes between Laparoscopic Sleeve Gastrectomy and Laparoscopic Roux-en-Y Gastric Bypass using the RAND36 questionnaire

Abstract: Bariatric surgery has been shown to improve a patient's QoL. More research is needed to explain the reasons why there was a difference between Sleeve and Bypass procedures in emotional changes to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…He concludes a clear improvement in the quality of life postoperatively, without noticing a significant difference between the group operated by sleeve gastrectomy and the group operated by gastric bypass Roux-en-Y [20], a result similar to that of Janik et al [19]. Other authors have used the SF-36 as a tool for measuring the quality of life and have noticed a significant improvement in the quality of life after bariatric surgery [9, 21, 22].…”
Section: Discussionmentioning
confidence: 75%
“…He concludes a clear improvement in the quality of life postoperatively, without noticing a significant difference between the group operated by sleeve gastrectomy and the group operated by gastric bypass Roux-en-Y [20], a result similar to that of Janik et al [19]. Other authors have used the SF-36 as a tool for measuring the quality of life and have noticed a significant improvement in the quality of life after bariatric surgery [9, 21, 22].…”
Section: Discussionmentioning
confidence: 75%
“…Improvement was comparable between LSG and LRYGB, except for physical functioning and general health perception for which RYGB was more beneficial [ 39 ]. In the short-term follow-up (1–2 years), authors report comparable outcomes with significant improvement of QoL after both LSG and LRYGB [ 40 , 41 ]. A study by Takemoto et al reported significant improvement in both mental and physical aspects of QoL 1 year after bariatric procedures, which remained stable during the following 5 years [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Amichaud et al and Charalampakis et al, [39]. In the short-term follow-up (1-2 years), authors report comparable outcomes with significant improvement of QoL after both LSG and LRYGB [40,41]. A study by Takemoto et al reported significant improvement in both mental and physical aspects of QoL 1 year after bariatric procedures, which remained stable during the following 5 years [42].…”
Section: Discussionmentioning
confidence: 96%